Was the Global Food Crisis Really a Crisis? Simulations versus Self-Reporting - Headey, Derek D. (International Food Policy Research Institute, 2011)
Have rising food prices hurt the poor, or helped them? So far, all answers to this question are based on simulation analyses by the World Bank, the Food and Agriculture Organization of the United Nations (FAO), and the US Department of Agriculture (USDA). These simulation studies almost invariably suggest that the rise in international food prices in 2007-08 substantially raised the number of poor or hungry people by anywhere from 60 to 160 million people.